Animation Video using Adobe Animate CC Application Based on Problem-based Learning - Rosita Dwi Ferdiani; Trija Fayeldi; Triayuningsih Permata Suci (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
So far learning has only used lecture and discussion methods, and has not implemented problem-based learning. Learning has not used learning media, especially animated video media so that students tend to get bored and less interested. Based on the analysis of student learning outcomes on sequences and series material, as many as 56% of students scored below the KKM. This study aims to develop learning media based on video animation to improve student learning outcomes that are valid, feasible, and effective. This media is a mathematics learning media made using Adobe Animate which can be accessed via computers, laptops, or cellphones. This study uses the ADDIE model which is carried out through several stages as follows: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. This research involved students of vocational high school consisting of 6 students of Class XI Fashion Design as a small group test subject and 20 students of Class XI Computer and Network Engineering as a significant test group. Based on research that has been done on the development of animated videos using the Adobe Animate CC application based on problem based learning, it can be concluded that the media is stated to be very valid, very feasible and very effective in improving students' abilities. Animated videos using the Adobe Animate CC application based on Problem Based Learning have an impact on increasing student learning abilities.